Uterine Transplantation: Ethical Considerations within Middle Eastern Perspectives. Issue 2 (15th May 2015) - Altawil, Zaid; Arawi, Thalia
Abstract: The field of reproductive medicine witnessed a breakthrough in September 2014 with the first successful live birth post uterine transplantation. This success represents the culmination of decades' worth of research on infertility and reproductive medicine. This subject of infertility gathers special attention in the Middle East, as childbearing is given paramount importance in the family unit. And as with any new medical advancement, Middle Eastern people look to their religious authorities for guidance. This paper describes the various ethical quandaries related to uterine transplantation, from a perspective of the religious and societal factors that are unique to the Middle East, and embeds them within the conversation of its alternative solutions.